2018
DOI: 10.1002/1873-3468.13108
|View full text |Cite
|
Sign up to set email alerts
|

Tau filaments in neurodegenerative diseases

Abstract: The ordered assembly of Tau protein into abnormal filamentous inclusions is a defining characteristic of many human neurodegenerative diseases. Thirty years ago, we reported that Tau is an integral component of the intraneuronal filaments of Alzheimer's disease. All six brain Tau isoforms make up those filaments. Twenty years ago, we and others showed that mutations in MAPT, the Tau gene, cause familial forms of frontotemporal dementia, thus proving that dysfunction of Tau protein is sufficient to cause neurod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 66 publications
1
103
0
3
Order By: Relevance
“…Hence the 3R/4R tau aggregates in AD have a conformation that is distinct from tau species containing only 3R or 4R tau. This was supported by the recent finding that pTau aggregates in AD, PiD and CBD are characterized by different tau molecular structures with different conformations [21,22,29,76]. Together, these findings suggest that the combination of both 3R and 4R tau isoforms in pTau aggregates in AD, DS with AD, and PART could result in the generation of a common tau conformation, or tau "strain", across these diseases that is then capable of interaction with the same protein co-factors, such as SCRN1.…”
Section: Discussionsupporting
confidence: 57%
“…Hence the 3R/4R tau aggregates in AD have a conformation that is distinct from tau species containing only 3R or 4R tau. This was supported by the recent finding that pTau aggregates in AD, PiD and CBD are characterized by different tau molecular structures with different conformations [21,22,29,76]. Together, these findings suggest that the combination of both 3R and 4R tau isoforms in pTau aggregates in AD, DS with AD, and PART could result in the generation of a common tau conformation, or tau "strain", across these diseases that is then capable of interaction with the same protein co-factors, such as SCRN1.…”
Section: Discussionsupporting
confidence: 57%
“…The microtubule-associated protein tau is implicated in the pathophysiology of a range of neurodegenerative diseases, but also has a role as a non-specific biomarker of neuronal damage. In a misfolded and phosphorylated state it is a principal component of diseaseassociated protein aggregates in a range of so-called "tauopathies" including Alzheimer's disease, corticobasal degeneration, progressive supranuclear palsy and some forms of frontotemporal dementia (49). Although not a classical pathological hallmark of prion disease, it has been shown that phosphorylated tau deposits are a prominent autopsy finding in some inherited prion diseases (50).…”
Section: Taumentioning
confidence: 99%
“…Tau protein is abundantly expressed in the nervous systems, especially in nerve cell axons, and intrinsically disordered with a low content of secondary structures [21]. Tau has six isoforms depending on patterns of alternative splicing of the exons 2, 3, and 10.…”
Section: Progresses In Investigation Of Tau Amyloidsmentioning
confidence: 99%